Prevalence and Management of Septic Shock among Children Admitted at the Kenyatta National Hospital, Longitudinal Survey. (17th December 2019) - Vekaria-Hirani, Varsha; Kumar, Rashmi; Musoke, Rachel N.; Wafula, Ezekiel M.; Chipkophe, Idris N.
Abstract : Background . Paediatric septic shock is a subset of sepsis associated with high mortality. Implementing the existing international Surviving Sepsis Campaign Guidelines 2012 (SSCG) have contributed to reduction of mortality in many places but these have not been adopted in our setting. The current study aimed at documenting the practice at a national referral hospital. Methods . A hospital based longitudinal survey carried out among 325 children from September to October 2016. Children aged 0 days (≥37 weeks gestation) to12 years were included. The aim was to determine the prevalence, audit the management and determine the outcome at 72 hours of septic shock among children admitted at the Kenyatta National Hospital (KNH). A standard questionnaire was used for data collection and Surviving Sepsis Guideline 2012 was used as a reference for auditing the management of septic shock. Data was stored in MS-EXCEL and analysed in STATA 12. Results . The prevalence of septic shock was 50 (15.4%), with a median age of 4 months. Septic shock was recognized by the attending clinician in 28 (56%). The level of care to children with septic shock was not to the level recommended by the SSCG 2012. Odds of being diagnosed with septic shock reduced with age (odds ratio 4.38 (1.7–11.0), p = 0.002 ) and no child aged above 60 months age was diagnosed with septic shock. The mortality was 35 (70%) at 72 hours of admission, with a median of 14 hours. Infants had the highest case fatality of 82.6%. It was found that lack of mechanical ventilation, and presence of hypotension at admission were associated with greater mortality (p values of 0.03 and 0.01 respectively). Conclusion . The prevalence rate of septic shock is 15.4% among children admitted at the KNH and is associated with high mortality. The advanced degree of shock contributed to mortality. The level of care at KNH was not to the level of SSCG 2012, and hence the need to include septic shock management guidelines/protocols in our local Kenyan paediatric guideline.